Preferential Colonization of Osteoblasts Over Co-cultured Bacteria on a Bifunctional Biomaterial Surface - Chu, Linyang; Yang, Ying; Yang, Shengbing; Fan, Qiming; Yu, Zhifeng; Hu, Xi-Le; James, Tony D.; He, Xiao-Peng; Tang, Tingting (Frontiers in Microbiology, 2018)
Implant-related infection is a devastating complication in clinical trauma and orthopedics. The aim of this study is to use a bifunctional biomaterial surface in order to investigate the competitive colonization between osteoblasts and bacteria, which is the cause of implant-related infection. A bone-engineering material capable of simultaneously facilitating osteoblast adhesion and inhibiting the growth of Staphylococcus aureus (S. aureus) was prepared. Then, three different co-cultured systems were developed in order to investigate the competitive colonization between the two cohorts on the surface. The results suggested that while the pre-culturing of either cohort compromised the subsequent adhesion of the other according to the ‘race for the surface’ theory, the synergistic effect of preferential cell adhesion and antibacterial activity of the bifunctional surface led to the predominant colonization and survival of osteoblasts, effectively inhibiting the bacterial adhesion and biofilm formation of S. aureus in the co-culture systems with both cohorts. This research offers new insight into the investigation of competitive surface-colonization between osteoblasts and bacteria for implant-related infection.